Phantasms - Saghafi, Kas (Bollettino Filosofico, 2021)
Taking into consideration the philosophical and psychoanalytic history of the term phantasm, Derrida in his late work provides for deconstruction a new definition of the «phantasm». Thinking the phantasm, Derrida argues, requires «a new logic» beyond logos. This paper attends especially to late use of the term phantasm in Derrida’s work – the phantasm of «living death» and the phantasm of «almightiness» – to tap into resources unexplored by the tradition and to demonstrate that the phantasm need not necessarily be attrached to sovereignty and have a negative valence. Keywords: Blanchot, Deconstruction, Derrida, Event, Phantasm